Analisis Tingkat Literasi Membaca Cerita Jataka Di SMA Bhakti Karya Kecamatan Kaloran Kabupaten Temanggung - Hartini, Sri (Pendidikan Dasar dan Manajemen Pendidikan, 2022)
This study aims to determine the level of literacy in reading jataka stories. The type and approach of research used in this study is a quantitative approach. In this study, the target of the study was Buddhist students in grades 10, 11, and 12 at SMA Bhakti Karya Kaloran District, Temanggung Regency with a total of 46. Techniques in data collection using questionnaires. The results showed that literacy activities at SMA Bhakti Karya were classified in the medium category with the largest number, namely 34 students in the medium category with a percentage of 74% while the level of reading jataka stories at SMA Bhakti Karya was also included in the medium category with the largest number of 35 students entering the medium category with a percentage of 76%.